PRACTICE TO POLICY: ASSESSING EVIDENCE-BASED DECISION-MAKING IN HEALTH POLICY IN GREATER MANCHESTER - Lazo, Kimberly Camille (PEOPLE: International Journal of Social Sciences, 2018)
In the context of health policy, knowledge translation is a key to maintaining a robust decision-making process. Literature suggests that knowledge has different purposes in the policy process, and multiple actors have various preferences over which knowledge to use in influencing their decision-making. Through a knowledge translation framework embedded in the assumptions of rational actor models, this research evaluates the relationship between policy and evidence, the role that knowledge plays within this interaction, and the factors that influence the knowledge translation in the health and social care policy in Greater Manchester. A mixed methods approach is used to analyse the Greater Manchester Health and Social Care Partnership and the organisations within it (to be completed over the Summer), to determine if collaborative working exemplified by this partnership is consistent with the theory of co-production and rational decision-making. The overall contribution of this research is to provide a small picture of what decision-making is like in the local level, in the midst of budgetary pressures and political agenda to provide effective solutions in the health policy context in Greater Manchester.